2013
DOI: 10.1021/ic401291a
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of Ternary Copper–Antimony Sulfide Nanocrystals

Abstract: Ternary copper-antimony sulfide nanocrystals (CAS NCs) have attracted increasing attention in photovoltaics and photoelectric nanodevices due to their tunable band gaps in the near-IR regime. Although much progress in the synthesis of CAS NCs has been achieved, the selective synthesis of CAS NCs with controllable morphologies and compositions is preliminary: in particular, a facile method is still in demand. In this work, we have successfully selectively synthesized high-quality CAS NCs with diverse morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 37 publications
1
57
1
Order By: Relevance
“…16,18 However, previous studies have reported that CuSbS 2 NC is an indirect band gap material. 17,24 A possible reason for the discrepancies between the theoretical and experimental band gaps is the presence/absence of impurities or defects in the CuSbS 2 NCs, as suggested by Kumar et al 7 In contrast to the CuSbS 2 and Cu 12 Sb 4 S 13 NCs, the Cu 3 SbS 4 NCs exhibited a behavior consistent with indirect band gap semiconductors (n = 1/2). In addition, the CuSbS 2 and Cu 12 Sb 4 S 13 NCs exhibited a gradual increase in absorbance in the NIR wavelength region.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…16,18 However, previous studies have reported that CuSbS 2 NC is an indirect band gap material. 17,24 A possible reason for the discrepancies between the theoretical and experimental band gaps is the presence/absence of impurities or defects in the CuSbS 2 NCs, as suggested by Kumar et al 7 In contrast to the CuSbS 2 and Cu 12 Sb 4 S 13 NCs, the Cu 3 SbS 4 NCs exhibited a behavior consistent with indirect band gap semiconductors (n = 1/2). In addition, the CuSbS 2 and Cu 12 Sb 4 S 13 NCs exhibited a gradual increase in absorbance in the NIR wavelength region.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Normally, the ligand likely plays a key role for the size controllable synthesis of CAS NCs. Most of the reports on CAS NCs synthetic scheme chose fatty amines as the ligand, while the sizes of the products were too large in the range from 20 nm to several micrometers, which limited their special performance in the application. In order to obtain smaller size of CAS NCs, Tachibana and co‐workers chose fatty amines and carboxylic acids as the coligands, CAS NCs with size range from 6 to 18 nm were obtained.…”
Section: Introductionmentioning
confidence: 92%
“…This was also investigated by other researchers [6][7][8]12], but the structure of underpotentially deposited Sb adlayer on Au(111) was not resolved on an atomic level. It is well known that Sb [13][14][15], Bi [16][17][18], etc. can be used to form bimetallic semiconductors.…”
Section: Introductionmentioning
confidence: 99%